Andrographolide contributes to the attenuation of cardiac hypertrophy by suppressing endoplasmic reticulum stress - Qingxin Tian; Jianlong Liu; Qin Chen; Mingxiao Zhang (Taylor & Francis Group, 2023)
AbstractContext Andrographolide (Andr) is a bioactive Andr diterpenoid extracted from herbaceous Andrographis paniculata (Burm. F.) Wall. ex Nees (Acanthaceae). Andr can relieve cardiac dysfunction in mice by inhibiting the mitogen-activated protein kinases (MAPK) pathway.Objective This study investigates the efficacy and underlying mechanism of Andr on cardiac hypertrophy in mice.Materials and methods Male C57 mice (20-25 g, 6-8 weeks) were divided into four groups (n = 10 mice/group) as sham group (sham operation), transverse aortic constriction (TAC) model group, TAC + Andr 100 mg/kg group and TAC + Andr 200 mg/kg group. Andr groups were given intragastric administration of Andr (100 and 200 mg/kg) once a day for 14 consecutive days. An in vitro hypertrophy model was established by adding 1 μM of Ang II to H9c2 cells for 48 h induction.Results In TAC-mice, Andr improved echocardiographic indices [reduced LVESD (30.4% or 37.1%) and LVEDD (24.8% or 26.4%), increased EF (22.9% or 42.6%) and FS (25.4% or 52.2%)], reduced BNP (11.5% or 23.6%) and Ang II levels (10.3% or 32.8%), attenuates cardiac fibrosis and reduces cardiac cell apoptosis in TAC mice. In vitro, Andr attenuated cardiomyocyte hypertrophy and decreased the protein expression of GRP78 (67.8%), GRP94 (47.6%), p-PERK (44.9%) and CHOP (66.8%) in Ang-II-induced H9c2 cells and reversed after endoplasmic reticulum (ER) stress agonist Tunicamycin (TN) treatment.Discussion and conclusions Andr was found to be an anti-hypertrophic regulator, which could attenuate cardiac hypertrophy by suppressing ER stress. It may be a new therapeutic drug for cardiac hypertrophy.